Novel coatings to reflect the sun's heat.
Heat from human activities can greatly influence climate change, with recent studies linking rising temperatures in cities to the solar absorption that occurs in buildings and homes. EU-funded scientists have developed a novel coating technology with high light reflectance that can help reverse solar absorption and mitigate the urban heat island effect.